Novel Mutations in Oleoyl‐PC Desaturase (ahFAD2B) Identified from New High Oleic Mutants Induced by Gamma Rays in Peanut. Issue 5 (10th August 2017) - Nadaf, H. L.; Biradar, Kavera; Murthy, G. S. S.; Krishnaraj, P. U.; Bhat, Ramesh S.; Pasha, Malik Ahmed; Yerimani, Abid S.
Abstract : To diversify the sources of the high‐oleate trait in peanut ( Arachis hypogaea L.), the broad‐based interspecific derivative with inherent resistance to major foliar diseases, GPBD‐4, was subjected to chemical (ethyl methanesulfonate) and physical (γ rays) mutagenesis, resulting in significant variation in fatty acid profile of mutant progenies as tested by gas chromatography in advanced (M4 ) generations. From these mutant progenies, two stable high‐oleic (>70%) mutant lines, GM 4‐3 and GM 6‐1, were chosen for molecular characterization of ahFAD2B by cloning and sequencing. We report here the identification of two novel mutations (1085A‐G and 1111G‐A) in oleoyl‐PC desaturase ( ahFAD2B ) of high‐oleic mutant line GM 6‐1 and the latter single transition 1111G‐A in another high‐oleic mutant line GM 4‐3. The deduced amino acid sequence comparison of the parental genotype, GPBD‐4, with normal‐oleic (∼50%) and high‐oleic (>70%) mutant lines indicated the common change from glycine to serine at 372 from start codon due to the common single‐nucleotide polymorphism (SNP, 1111G‐A) observed in both the high‐oleic mutant lines. Another amino acid change from glutamate to glycine was also found in the mutant line GM 6‐1 because of the additional SNP it had at 1085A‐G in the coding region of ahFAD2B . These novel mutations identified in the new high‐oleic mutant lines could be used for marker‐assisted selection for the high‐oleate trait, and these foliar disease‐resistant, high‐oleic mutant lines could serve as additional valuable genetic resources for oil quality improvement in future peanut breeding programs.